Pengaruh profitabilitas, struktur aktiva dan ukuran perusahaan terhadap struktur modal pada perusahaan properti dan real estate yang terdaftar di BEI 2013-2017 - Ariyanto Ariyanto (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2020)
The purpose of this study is to describe (1) the effect of profitability, asset structure and company size on capital structure simultaneously, (2) Effect of profitability on capital structure, (3) Effect of asset structure towards capital structure, (4) Effect of firm size on capital structure. This research belongs to the type of correlational research. The population in this study is the Property and Real Estate Services Company listed on the Stock Exchange in 2013-2017 which has a total assets of at least 10 trillion. To determine the sample, researchers use financial statement data. The research sample was obtained from financial data found at www.idx.com. The research population was 8 companies in 5 periods. The data analysis technique used is the classic assumption test, multiple regression test, simultaneous F test, t test and determination test.